A Preliminary Comparison Suggests Poor Performance of Carbon Fiber Reinforced Versus Titanium Plates in Distal Femoral Osteotomy. Issue 3 (October 2018) - Fragomen, Austin T.; McCoy, Thomas H.; Fragomen, Fiona R.
Background: Carbon fiber-reinforced (CFR) polymer implants have theoretical advantages over titanium plates. Questions/Purposes: The aim of the present study was to assess our early outcomes with CFR plates in lateral opening-wedge distal femoral osteotomy to correct valgus lower limb malalignment. We asked the following: (1) Did the CFR polymer implant change time to union when compared with the titanium implant? (2) Did the incidence of displacement of medial cortical fractures differ between the implants? (3) Did the incidence of complications differ between the two techniques, and did other factors, such as bone graft material used, affect healing? Methods: A retrospective review of 16 limbs treated with an opening-wedge distal femoral osteotomy for genu valgum using either titanium ( n  = 10) or CFR plates ( n  = 6) was performed. Patient and clinical covariates as well as the primary outcome of time to union and secondary outcome of fracture displacement were collected and analyzed. Results: Those treated with CFR plates had longer times to union than did those in the titanium-treated group (median, 121.5 vs 81.5 days, respectively). The incidence of fracture displacement was higher in the CFR plate-treated group (CFR, n  = 5/6; titanium, n  = 1/10). Although the CFR plate-treated group had a 33% nonunion incidence while the titanium group had no nonunions, the study lacked the power to show significance. Bone graft material used did not affect outcome. Complication rates were higher in the CFR plate-treated patients. Conclusion: The CFR plate was associated with a longer time to unite and higher fracture displacement rate than the titanium plate. As this is a retrospective case series, further research is required to confirm these results and clarify best practices in plating of distal femoral osteotomy for deformity correction.